PERFORMANCE ANALYSIS OF EMPLOYEES IN REGIONAL OFFICES OF THE MINISTRY OF LAW AND HUMAN RIGHTS - Anisa Yani; Karona Cahya Susena; Mimi Kurnia Nengsih (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
The purpose of the study is to determine the employee performance in the Regional Office of the Ministry of Law and Human Rights (HAM) in Bengkulu. This research is a qualitative study, the informants used in this study were 5 employees of the Regional Office of the Ministry of Law and Human Rights (HAM) in Bengkulu, the data collection techniques used were interviews and the analytical method used was descriptive analysis method. The results of this study indicate that leadership factors can improve the employee performance in the Regional Office of the Ministry of Law and Human Rights (HAM) in Bengkulu, because the leader always maintains good relations with his subordinates and always cooperates, besides that the leader also provides direction and support in working therefore employees can improve their performance. Motivation factor that can be done by the Regional Office of the Ministry of Law and Human Rights (HAM) in Bengkulu by providing supervision to its employees and also providing job guarantees by way of promotion. A safe and comfortable work environment will improve employee performance, as well as in the the Regional Office of the Ministry of Law and Human Rights (HAM) in Bengkulu. The work environment provided is a physical and non-physical work environment.